2023
DOI: 10.1007/s00270-023-03420-2
|View full text |Cite
|
Sign up to set email alerts
|

Possible use of Digital Variance Angiography in Liver Transarterial Chemoembolization: A Retrospective Observational Study

Abstract: Purpose Digital variance angiography (DVA), a recently developed image processing technology, provided higher contrast-to-noise ratio (CNR) and better image quality (IQ) during lower limb interventions than digital subtraction angiography (DSA). Our aim was to investigate whether this quality improvement can be observed also during liver transarterial chemoembolization (TACE). Materials and Methods We retrospectively compared the CNR and IQ parameters of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Nevertheless, a recent study suggests that the quality advantage of DVA can also be observed in lower limb interventions, where selective angiography is applied [15]. The quality reserve of DVA was also demonstrated in carotid angiography [23] and prostatic artery embolization [16], and liver transarterial chemoembolization [27]. These observations suggest that the dose management would be possible also in these endovascular interventions, but the results cannot be generalized without further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a recent study suggests that the quality advantage of DVA can also be observed in lower limb interventions, where selective angiography is applied [15]. The quality reserve of DVA was also demonstrated in carotid angiography [23] and prostatic artery embolization [16], and liver transarterial chemoembolization [27]. These observations suggest that the dose management would be possible also in these endovascular interventions, but the results cannot be generalized without further investigations.…”
Section: Discussionmentioning
confidence: 99%